EcoRI restriction endonuclease map of the composite R plasmid NR1. - Tanak, N (1976)
A physical map of the composite R plasmid NR1 has been constructed using specific cleavage of deoxyribonucleic acid (DNA) by the restriction endonuclease EcoR-. Digestion of composite NR1 DNA by EcoRI yields thirteen fragments. The six largest fragments (designated A to F) are from the resistance transfer factor component that harbors the tetracycline resistance genes (RTF-TC). The seven smallest fragments (designated G to M) are from the r-determinants component that harbors the chloramphenicol (CM), streptomycin-spectinomycin (SM/SP), and sulfonamide (SA) resistance genes. The largest fragment of several RTF-TC segregants of NR1 that have deleted the r-determinants component is 0.8 X 10(6) daltons larger than fragment A of composite NR1. Only a part of fragment H of the r-determinants component is amplified in transitioned NR1 DNA in Proteus mirabilis, which consists of multiple, tandem sequences of r-determinants attached to a single copy of the RTF-TC component. Both of these changes can be explained by the locations of the excision sites at the RTF-TC: r-determinants junctions that are involved in the dissociation and reassociation of the RTF-TC and r-determinants components. The thirteen fragments of composite NR1 DNA produced by EcoRI have been ordered using partial digestion techniques. The order of the fragments is: A-D-C-E-F-B-H-I-L-K-G-M-J. The approximate locations of the TC, CM, SM/SP, and SA resistance genes on the EcoRI map were determined by analyzing several deletion mutants of NR1.